Surface rupture associated with a moderate intraplate earthquake: the Mw 6.2 Parina event (December 1st, 2016) in the Peruvian Altiplano - Aguirre Alegre, Enoch Matthew (2018)
Trabajo presentado en el “6th Colloquium on historical earthquakes & paleoseismology studies : Their contribution to the knowledge of the long-term seismic activity and to seismic hazard assessment”, 24-26 October 2018, Han-sur-Lesse, Bélgica.